A psicologia organizacional na visão dos alunos de psicologia - Rittner, Carmem Lúcia Arruda (2008)
The aim of this research was to find out how do students understand the action field concept of Organizational Psychologists. Also how students in their professional practices represented the possibility of making interventions concerned to the improvement of social organizations as well as individuals This research has been developed with Psychology students from private university in Sao Paulo Brazil and it was based on the Social Representation Theory. To understand the Organizational Psychology phenomenon, as the social representation object, meant, above all, to identify the mechanisms that certain groups use to integrate this object (action field concept of Organizational Psychologists) and other mechanisms already presented in their knowledge (anchorage) as well as to identify the images and expressions that the groups materialize in their object s communication process (objetivação).The data were obtained from questionnaires and from an exercise of free associations evocations from three words were analyzed : Psychology, Psychologist and Organizational Psychology The content analysis of students response to the questions was made by the processing of the ALCEST (Alceste Computer Program) .and the analysis of frequency and order of evocations realized by the EVOC software . The results show that the social representation of Organizational Psychology by the students of Psychology is homogeneous and suggests a concept based in helping and listening attitude. Ethical considerations are nuclear to the speech of students. Conventional practices are peripheral of such representation. Conclusions point out that, although the results show in some extent that the social representation, by students of Psychology is been built in the direction of a more significant social participation, those improvements shall be accelerate to cope with the transformation of organizations in a globalized world